Reconstruction of historical datasets for analyzing spatiotemporal influence of built environment on urban microclimates across a compact city. (October 2017) - Peng, Fen; Wong, Man Sing; Ho, Hung Chak; Nichol, Janet; Chan, Pak Wai
Abstract: The high-rise/high-density environment of a compact city can influence the microclimate resulting in lower living quality. Previous studies have analyzed the relationships between high-rise/high-density environment and microclimates, by either a temporal study or a spatial approach, while a strategy for investigating the spatiotemporal relationship has yet to be developed. This study initiated a set of innovative strategies to map the historical built environment/microclimates of a compact city, with a spatiotemporal approach to analyze the relationships between building structures and urban climates, for developing a sustainable protocol for future urban planning. Three major components were reconstructed, including 1) the annually averaged Land Surface Temperature (LST) for determining the relative temperature across a compact city; 2) 3D building datasets for representing the building morphology; and 3) sets of urban morphological data derived from building datasets for analyzing microclimate and thermal distress. There are high correlations between observed and predicted LSTs (R = 0.64 to 0.89), with mean absolute error (MAE) of annually averaged LST ranging 0.49 °C–2.60 °C, and root mean square error (RMSE) ranging 0.62 °C–2.98 °C. There are low errors for reconstructing building data, in which MAEs and RMSEs of an open space are 0.41 m–1.23 m and 0.78 m - 1.46 m; and for an area with buildings are 0.81 m–3.25 m and 1.06 m - 5.92 m. The spatiotemporal estimation indicated areas with improved air ventilation through years can significantly reduce an additional 0.12 °C - 1.09 °C than the areas without improvement, while areas with an increase in shades through years have 0.6 °C–0.76 °C higher reduction of relative temperature. Highlights: Reconstructed the historical temperature maps across Kowloon Peninsula based on Landsat images. Reconstructed 3D built environment with aerial photographs. Areas with more shades through years have greater contribution to reduce local heat. Areas with more ventilation through years have greater contribution to reduce local temperature. Variation of building heights is suggested to integrate both shading effects and air ventilation to develop a compact city.